Gardenias at a Glance - Sydney Park Brown; Joan Bradshaw (EDIS)
Circular 1098, a 2-page fact sheet by Sydney Park Brown and Joan Bradshaw, provides description, cultural requirements, problems and propagation for this popular plant with fragrant white flowers and glossy dark leaves. Published by the UF Department of Environmental Horticulture, October 2007.